Interracial Adoption: One Family’s Journey - Nahwegahbow, Barb; Lee, Jeff; Lee, Bill; Lee, Cecelia; Lee, Barbra (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2016)
A crucial concern regarding the adoption of Indigenous children into “white” families is the separation of the child from her/his Indigenous community and the struggles for the children involved. This paper examines the struggles faced by one Anishinawbe child and his family, the Lees, to come to terms with this dynamic when they adopted him in the early 70s. After the adoption they came to understand themselves as a family that was no longer “white”, one that faced unique challenges as well as opportunities. The initial strategy of the parents was to maintain his contact with the Indigenous community and culture. However, it became apparent that they had to find a way to Indigenize themselves as well. This was accomplished with the assistance of the Indigenous community. This story, unfortunately, does not reflect the majority of transracial adoptions. It is a hopeful one but also raises questions for the role of Indigenous communities, adoptive parents and in particular for policy makers.